Post-PKS enzyme complexes. Issue 11 (13th August 2019) - Gober, Redding; Wheeler, Ryan; Rohr, Jürgen
Abstract : This review highlights the protein–protein interactions between type II post-PKS tailoring enzymes with an emphasis on gilvocarcin and mithramycin. Abstract : Natural products are produced by bacteria, plants, and fungi and have yielded some of the most clinically active and widely used drugs available. Several of the natural products that are produced by type II PKSs have novel scaffolds or unique rearrangements that are, in large part, due to the post PKS enzymes. Protein–protein interactions between post-PKS tailoring enzymes hamper the use of combinatorial biosynthesis in the development of novel natural product-derived drugs. Several co-dependent post-PKS enzymes have been characterized in nature, but their significance in regards to complex formation and co-dependence has been largely overlooked. Here, we report an in-depth analysis of two such post-PKS pathways, gilvocarcin and mithramycin, for which indications exist to postulate multienzyme complexes to facilitate substrate protection and channeling.